Incidence of surgical site infection in elective inguinal hernia surgery and factors affecting it - Shah, Zahid H. Z.; Ali, Syed A.; Qaisaruddin, Syed (International Surgery Journal, 2024)
Background: Surgical site infections (SSIs) are a significant concern in surgical patients. The present study aims to estimate the incidence and evaluate the risk factors, microbiology, prevention strategies, and management of SSIs in patients undergoing elective inguinal hernia repair. Methods: This prospective observational study included 1053 patients who underwent elective inguinal hernia repair at our institution. Patient demographics, surgical characteristics, and outcomes were collected and analysed. Independent risk factors for SSI were identified by univariate and multivariate analyses. Results: Thirty-one patients developed SSIs within 30 days after surgery, resulting in an overall SSI rate of 2.94%. The most common microorganism isolated from SSI was Staphylococcus aureus. Identifiable risk factors associated with SSIs included age ≥65 years, body and mass index (BMI) >24.6 kg/m2, current smoking and diabetes mellitus. Conclusions: The study highlights the importance of identifying high-risk patients and implementing preventive measures to reduce the incidence of SSIs in elective inguinal hernia surgery. The findings suggest that age ≥65 years, BMI >24.6 kg/m2, current smoking and diabetes mellitus are risk factors for SSIs. The study also emphasizes the importance of proper skin preparation and antibiotic prophylaxis in reducing the risk of SSIs.